Temporal Variations in Calls for Police Service During COVID-19: Evidence From China - Dai, Mengliang (Crime & delinquency, 2022)
This study examined the temporal variations in calls for service before, during, and after the COVID-19 pandemic lockdown in China using a sample of 37,124 police service calls made from January 1, 2019, to December 31, 2020 to a 110 command center in a county-level city in Hubei Province. There was a significant temporal effect, and the calls for service peaked between 08:00 and 19:59 throughout the entire period. The busiest hours of the day for calls for police service were between 12:00 and 19:59, and the calls peaked between 12:00 and 15:59 during the lockdown. The distribution of calls by weekday showed no significant pattern, with the exception of traffic-related calls. The results are discussed from the perspective of routine activity theory.